EARNINGS MANAGEMENT: DETERMINANT FACTORS AND STOCK PRICE IN DEVELOPING MARKET - Zaenal Fanani (Jurnal Keuangan dan Perbankan, 2009)
The aim of this study was to prove whether manager coped its earnings for the purpose ofinformative or target opportunistic. Research also investigated whether investment opportunity setinfl uenced the choice of manager to report as opportunistic to hide performance, or to report earningmore informative concerning with debt, political cost, market share, and earning. Sample of thisresearch was chosen by using purposive sampling of 350 manufacturing business listed in the JakartaStock Exchange, started from 1997 up to 2002. Structural Equation Modeling (SEM) by using programof Analysis of Moment Structures (AMOS) was considered as the appropriate statistical technique toexamine pattern relation of formed model. The results showed that earning management conductedby manager in Developing Market such as Indonesia represented informative earning managementwhich meant all investors had more own belief in earning reporting, but this research could notprove that company owning high investment opportunity set tended to conduct informative earningmanagement.